(untitled) - Carpenter, Malcolm B. (Baltimore, 1978)
This this textbook for medical students, about Nervous System anatomy and histology
Keywords: Central nervous system,Neuroanatomy,Hệ thần kinh trung ương,Nervous system,Phẫu thuật thần kinh,Hệ thần kinh; Anatomy and Histology,Giải phẫu học và mô học